(untitled) (Styles of Communication, 2025)
In today’s digital age, where information spreads rapidly across social media platforms, disseminating health-related fake news has become a pervasive issue. Ioana Moldovan’s book, "Health-related Fake News: Case Study: Online Health Information Seeking and Sharing Behavior on Social Media among Romanian Retirees Aged 50+ during the Covid-19 Pandemic," provides an insightful and thought-provoking look into the complexities of health-related fake news in the online sphere.